Hubungan Persepsi Penyakit dan Durasi Menderita terhadap Manajemen Perawatan Diri pada Penderita Diabetes Mellitus - Boby Febri Krisdianto; Hema Malini; Silvia Zuela (NERS Jurnal Keperawatan)
Self-care management is crucial for preventing complications in individuals with diabetes mellitus, which is influenced by various factors, including disease perception and the duration of diabetes. This study aims to examine the relationship, direction, and strength of the association between disease perception, duration of illness, and self-care management in patients with type 2 diabetes mellitus. The study employed a quantitative correlational design with a cross-sectional approach, involving 74 respondents selected through purposive sampling. Data were collected using the Brief Illness Perception Questionnaire (B-IPQ) and the Summary of Diabetes Self-Care Activities (SDSCA-Revised). Data analysis was conducted using the Spearman Rank test. The findings showed that the average score for disease perception was 48.59, with an average illness duration of 5.00 years, and an average self-care score of 48.58. A significant positive correlation was found between disease perception and self-care management (p-value = 0.00), while no significant correlation was found between the duration of diabetes and self-care management (p-value = 0.132). These results suggest that enhancing patients' perception of their disease may improve self-care management. It is recommended that more intensive and targeted educational interventions be implemented to improve patients' positive perceptions and encourage more consistent self-care practices.